The quest to expand the coverage of public health insurance in the occupied Palestinian territory: an assessment of feasibility and sustainability using a simulation modelling framework. (March 2019) - Awawda, Sameera; Abu-Zaineh, Mohammad; Ventelou, Bruno
Abstract: Background: In their quest for universal health coverage (UHC), many developing countries explore alternative financing strategies to address the potential budgetary impact of health coverage expansion (for example, deferred debt versus current finance through taxation or premiums). Given the limited fiscal space, these policies may have different implications for fiscal sustainability and may worsen intergenerational inequality. Methods: We assessed the impact of UHC on fiscal sustainability and intergenerational inequality using an overlapping generations model within a general equilibrium framework, which we calibrate using data from the Palestinian Expenditures and Consumption Survey (PECS-2011) and the Social Accounting Matrix (SAM-2011). Fiscal sustainability is assessed using a prudent debt–GDP level of 39%. Intergenerational inequality induced by different policies is assessed by comparing the relative incremental burden (RIB) borne by each generation following the policy adjustment. Findings: In the absence of any policy adjustment, an ad hoc expansion of health coverage would increase the debt–GDP level to 15% above the prudent level. This indicates that the UHC fiscal stance may be financially unsustainable in the long run, therefore calling for a policy adjustment. Among the policies we examined, UHC finance through the increase of premiums (whether current or deferred) seems to be unsustainable and may further widen intergenerational inequality (RIB∈[3, 6]). By contrast, current finance through indirect taxes helps to restore a prudent debt–GDP level and seems to be associated with a lower level of intergenerational inequality than deferred-debt finance through direct taxation (RIB of 1·25 and 5, respectively). Interpretation: Among the policy options assessed, the current indirect taxation emerged as the best policy option in terms of its impact on both fiscal sustainability and intergenerational inequalities. However, from a policy perspective, the capacity of governments to raise additional revenues might be constrained in the short-term. Under such circumstances, deferred-debt finance may be preferred—a situation in which policy makers may have to trade fiscal sustainability against intergenerational inequality. Funding: The A*MIDEX project (number ANR-11-IDEX-0001-02) funded by the French Government programme Investissements d'avenir, managed by the French National Research Agency (ANR).